Toward a multidimensional indicator of resident-oriented sustainable development: The case of slum areas in Mumbai - Kitsuki, Akinori; Managi, Shunsuke (Frontiers in Sustainability, 2022)
This paper proposes a framework for weighting priority for the multidimensional domains of slum development from the viewpoint of residents. The weights estimated by our framework can be interpreted as marginal utility, and multiplying satisfaction scores in each domain of development by these weights yields residents’ utility from slum development. The proposed approach is carried out by accessing residents’ needs for slum development in Mumbai, India, where more than 5.2 million residents live in slum areas. Using the dataset obtained from a questionnaire survey that we conducted with slum residents in March 2019, we estimate marginal utilities for 23 domains of slum development. The results show that (1) slum residents most wish to improve development projects about human capital (health and education), electricity, and drinking water, even if they have already been highly satisfied, (2) they feel the least satisfaction with public toilets and place high priority on projects involving public toilets, (3) the sewage system has low priority with low satisfaction, but this priority increases as slum residents become better off, (4) the projects on social development and protection are highly satisfied and generally ranked low in terms of marginal utilities, and (5) air pollution and working conditions are also concerns of slum residents, especially as these residents become better off. It is expected that the framework used in this paper can be used to extract the problems of urban development and to track the progress of development plans from the viewpoint of residents.